2016
DOI: 10.1177/0004563215626952
|View full text |Cite
|
Sign up to set email alerts
|

Transient human anti-mouse antibody generated with immune enhancement in a carbohydrate antigen 19-9 immunoassay after surgical resection of recurrent cancer

Abstract: A novel transient human anti-mouse antibody generated with immune activation in a carbohydrate antigen 19-9 immunoassay using an AIA 1800 analyser was identified in a patient with rectal cancer after surgical resection. These findings demonstrate the importance of monitoring tumour markers in patients after treatment with mouse monoclonal antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…HAMA production is induced by various stimuli, including administration of mouse‐derived vaccines, which was a common practice when purification techniques were insufficient. HAMA is also produced after administration of molecular targeted drugs. In the present study, we found a difference in measured values in many individuals, possibly due to heterophilic antibodies, even without any history of administration of molecular targeted drugs.…”
Section: Discussionsupporting
confidence: 49%
“…HAMA production is induced by various stimuli, including administration of mouse‐derived vaccines, which was a common practice when purification techniques were insufficient. HAMA is also produced after administration of molecular targeted drugs. In the present study, we found a difference in measured values in many individuals, possibly due to heterophilic antibodies, even without any history of administration of molecular targeted drugs.…”
Section: Discussionsupporting
confidence: 49%
“…Other studies have shown that heterophilic antibodies and a low‐molecular‐weight interference result in the false positives of CA19‐9 concentration 8–10 . Further, human anti‐mouse antibody generation after immunotherapy (panitumumab and cetuximab) results in an increase of CA19‐9 concentrations in a patient with rectal cancer after surgical resection 11 . In the current case report, the patient's rheumatoid factor was within the reference range.…”
Section: Discussionsupporting
confidence: 48%
“…8 , 9 , 10 Further, human anti‐mouse antibody generation after immunotherapy (panitumumab and cetuximab) results in an increase of CA19‐9 concentrations in a patient with rectal cancer after surgical resection. 11 In the current case report, the patient's rheumatoid factor was within the reference range. The patient did not have any autoimmune disease, did not receive any immunotherapy, and tested negative for autoantibodies.…”
Section: Discussionmentioning
confidence: 56%
“…Based on these findings mannan-binding protein cannot be used as a binding matrix to immunoprecipitate antigen-loaded IgM molecules 35 . Other potential alternatives might be the use of secondary agarose-bound anti-IgM IgG antibodies 46,47 or use of surface-activated magnetic beads 48 . IgG antibodies directed against IgMs could be chemically crosslinked to agarose A or agarose G in order to reduce the extent of eluted antibody together with the antigen of interest.…”
Section: Discussionmentioning
confidence: 99%